Initial optimization and series evolution of diaminopyrimidine inhibitors of interleukin-1 receptor associated kinase 4. Issue 16 (15th August 2015) - Seganish, W. Michael; McElroy, William T.; Herr, R. Jason; Brumfield, Stephanie; Greenlee, William J.; Harding, James; Komanduri, Venukrishnan; Matasi, Julius; Prakash, Koraboina Chandra; Tulshian, Deen; Yang, Jinhai; Yet, Larry; et al.
Graphical abstract